Pengujian Variabel Mediasi Stres Kerja Terhadap Kinerja Karyawan Di Perusahaan Garmen - Zulfa, Nada Intania; Suryawardana, Edy; Ariefiantoro, Teguh; Mulyantomo, Edy; Kusnilawati, Nunik (Fakultas Ekonomi, Universitas Semarang, 2025)
This research aims to test or find out how much influence the workload variable and work environment have on employee performance which is mediated by the work stress variable. This test was carried out using a questionnaire method on the performance of employees in the production and packaging fields. The number of samples in this research was 100 respondents using a purposive sampling method, namely determining samples whose sample size was not yet known. The analytical tools used are path analysis, outer model analysis, inner model analysis and hypothesis testing with the help of SmartPLS 4.1.0.3 software. The results of this research show that workload and work environment have a positive and significant effect on employee performance, workload and work environment have a positive and significant effect on work stress, work stress has a positive and significant effect on employee performance. The indirect effect shows that workload and work environment influence employee performance through work stress.